Social Value Systems and the Mental Health of International Students During the COVID-19 Pandemic - Humphrey, Ashley; Forbes-Mewett, Helen (Journal of International Students, 2021)
Australian universities are understood to have the highest number of international students per capita worldwide. The sector contributes over $40 billion to the national economy and sustains many thousands of jobs. Despite their importance to the Australian economy and society, international students are often overlooked in mainstream health promotion and support services. Of the many difficulties and hardships international students experience, mental health presents a significant problem. Evidence indicates that the mental health of international students was declining before the COVID-19 pandemic took hold in Australia. The impact of the pandemic appears to have exacerbated this issue. Our findings from an online survey (n=135) and semi-structured interviews (n=20) reinforce the importance of international students maintaining close social connections for optimizing their mental health. They also bring clarity to the challenges students from highly socially engaged (collectivistic) cultures face, when studying in individualistic environments like Australia amid the COVID-19 pandemic.